IDENTITAS KOTA BANDUNG PADA BATIK KOMAR BERDASARKAN TEORI KEVIN LYNCH - Nukke Sylvia; Denta Mandra Pradipta B (Universitas Mercu Buana, 2019)
Identity is a characteristic or to the repertoire of a place, which makes someone recall and wants to visit again where they are intended because it has differences with other places because it has character and uniqueness. Identity is a very important fundamental thing. This is because identity is something that is used to recognize, distinguish a place from another place Kevin Lynch, good city form (1984; 131). According to RI Minister of Home Affairs regulation No. 4 years old 1980, the City is a place that has administrative boundaries such as municipalities and administrative cities. The city also means an urban living environment that has non-agrarian characteristics, for example, the district capital, the capital of the sub-district which functions as the center of growth. One that has these characteristics is the city of Bandung, the city of Bandung is one place that has its own uniqueness and character, both in places of tourism, food, and other foods. One of the places visited by many local and foreign tourists in searching for souvenirs or souvenirs is Batik. One of the famous Batik venues in Bandung is Komar Batik, Batik Komar is one place that produces Batik with Bandung City motif. Therefore the author wants to examine the Bandung City motif made by Batik Komar with the theory of Kevin Linch so that the history of the Bandung Batik can be maintained. After producing the Bandung Batik analysis, it can be concluded that Batik Komar as a batik maker reflects the identity of Bandung City.